Modeling of 120W Monocrystalline Photovoltaic Module using MATLAB Simulink - Siti Amely Jumaat; Adhwa Amsyar Syazwan Ab Majid; Mohd Noor Abdullah; Nur Hanis Radzi; Rohaiza Hamdan; Suriana Salimin (Institute of Advanced Engineering and Science, 2018)
This project aims to model a solar Photovoltaic (PV) Module using MATLAB Simulink. In Renewable Energy (RE) field, many studies have been carried out to determine the level of efficiency and performance of a specific PV module. Therefore, this research will carry out the modeling of the 120W Monocrystalline Photovoltaic Module by Su-Kam Solar using MATLAB Simulink to determine the efficiency and performance. The input parameters that consists of Solar Irradiance (G) and Temperature (T) data will be collected at location 1.8635° N, 103.1089° E which is in Parit Raja, Batu Pahat, Johor. The results are shown in I-V curve and P-V curve and compared with the theory of I-V and P-V curve. Other than that, the PV module have different performance in different value of irradiance and temperature. Lastly, the PV Module is work efficiently and full performance at Standard Test Conditon (STC).